Plan de negocios para la implementación de una empresa que desarrolla proyectos tecnológicos (domótica) para hogares, edificios y oficinas en la ciudad de Quito - Herrera Espinoza, Jhordan Alexander (2016)
The implementation of a company that provides technology solutions for the home through the comfort, safety and energy savings represents an innovative idea that has not been developed intensively in the country. The concept started on the basis that left the statistical information obtained about consumer habits and needs of comfort that stand today Ecuadorian families. Therefore, the offer proposed by the company Smart Living is to provide a modern space where technology is the main attraction of a home or office. Concepts such as ambient sound, air conditioning in the house or home automation devices, coupled with the differentiating elements such as service and call center specialist will be part of the comprehensive solution proposed by the company. To do this, the company will focus on Smart Living the population of the city of Quito living in the northern sector and Cumbayá Valley, where the head of household is independent professional, technical, manager or business owner and has an average monthly income of over USD 3,000. Additionally, the main strategy of the company to reach the market described above, it will be a best value approach where both the service and the product to a small range of customers with the best value-price bid. Clearly, to achieve these objectives, the company will require a team capable enough and ready to provide quality service and offer advice both on the technical side as part of interior design. To do this, is needed an organizational circular structure at the interface between operational and administrative aspects of the company there was formulated. Finally, the project investment will be funded at 40%; while the remaining 60% is a contribution of the project author and an expert in automation who will be part of the project management team.